2022
DOI: 10.1111/cts.13295
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics profiles of enteric‐coated mycophenolate sodium in female patients with difficult‐to‐treat lupus nephritis

Abstract: Relapsed or resistant lupus nephritis (LN) is considered a difficult-to-treat type of LN, and enteric-coated mycophenolate sodium (EC-MPS) has been used in this condition. Therapeutic drug monitoring using the area under the plasma mycophenolic acid concentration from 0 to 12 h postdose (MPA-AUC 0-12h ) ≥45 μg.h/ml is a useful approach to achieve the highest efficiency. This study assessed EC-MPS's pharmacokinetic (PK) and pharmacodynamic (PD) profiles and investigated an optimal level of the single time point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…MPA was administered to patients during both the induction and maintenance phases. The majority of the studies examined the PK parameter of MMF, while Chariyavilaskul et al 29 used EC-MPS and Lertdumrongluk et al 21 investigated both MMF and EC-MPS. Concurrent immunosuppressive drugs were calcineurin inhibitors (ciclosporin and tacrolimus), 24 25 belimumab, 30 mizoribine 25 and cyclophosphamide.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MPA was administered to patients during both the induction and maintenance phases. The majority of the studies examined the PK parameter of MMF, while Chariyavilaskul et al 29 used EC-MPS and Lertdumrongluk et al 21 investigated both MMF and EC-MPS. Concurrent immunosuppressive drugs were calcineurin inhibitors (ciclosporin and tacrolimus), 24 25 belimumab, 30 mizoribine 25 and cyclophosphamide.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the limited evidence regarding the association between MPA C 0 and clinical response in the existing studies (total five studies reported mean C 0 and response rate), a meta-regression analysis for MPA C 0 was not performed. Nevertheless, various studies have reported divergent target MPA concentrations, with C 0 of 2.0–2.4 mg/L, 27 C 0.5 ≥2.03 mg/L 29 and C 1 ≥13 mg/L 22 being associated with a more favourable treatment response. In the context of our meta-analysis, patients demonstrating a renal response displayed an average C 0 of 2.5±1.7 mg/L, contrasting with 1.5±1.3 mg/L among non-responders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minor part of MPA is later metabolized to acyl-glucuronide (AcMPAG) [ 9 ]. MPA selectively and reversibly inhibits an enzyme called inosine monophosphate dehydrogenase (IMPDH), which plays a key role in the de novo purine biosynthesis [ 7 , 10 ]. By blocking the pathway above, MPA inhibits T and B lymphocytes from proliferating, thus causing immunosuppression to prevent graft rejection [ 7 ].…”
Section: Introductionmentioning
confidence: 99%